Penataan Kawasan Wisata Dakwah Okura Dengan Pendekatan Arsitektur Ekspresionisme - Edi Kurniawan; Wahyu Hidayat; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Dakwah Okura Tourism is a sunnah sport tours located in the village of Okura, Rumbai district. Dakwah Okura Tourism is the first sharia tourist attraction using the concept of sunnah sports as their tourist activity. There are sunnah sports recommended in Islam, in a hadith of the Prophet, those 3 types of sports are swimming, horseback riding and archery. In order to keep the aesthetics and the comfort of the user, there should be an optimization at this tourist area, so thatthe infrastructure could work synergistically and comprehensively to support more adequate activities and to complete some sunnah sports activities. This design method used the theme of expressionism architecture as the form of building architecture that could realize a concept of how the building are able to accommodate well and becoming the identity of the region and having anattractive aesthetic. The design of this tourist area is aimed to introduce the sunnah sports to the community, especially Riau community, so that the community are able to get closer to the sunnah, which is recommended by the Prophet Muhammad Shallallahu 'Alaihi Wasallam. The result of this design is the visitors can feel the differences that exist in each building and feel the sensation as well as expressing their emotions or feelings through the form. There are 3 functions that exist in this area, which is: primary function, secondary function and support function. Activities in this primary function are: horseback riding, swimming, archery and airsoft gun/paintball, the secondary function is in the form of trade and services, the supporting function is in the form of treatment, management and service.Keyword: Aesthetics, Dakwah Okura, Expressionism Architecture, Sunnah Sports